MOTIVASI UNI EROPA MEMBERIKAN BANTUAN DALAM BENTUK HIBAH KEPADAINDONESIAMELALUI PROGRAM ARISE PLUS INDONESIA TAHUN 2018-2023 - Jelita Sari; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this research is to explain and find out the development of cooperation between Indonesia and the European Union through the ARISE Plus Indonesia Program. and knowing the specific purpose of the European Union providing grant funds to Indonesia through the ARISE Plus Indonesia Program.This study uses the perspective of liberalism, the level of international system analysis, the theory of comparative advantage, the method used is qualitative by connecting the causes and effects of research that occurs using library research techniques, and this study collects data through secondary data.The results of this research can be obtained that ARISE Plus Indonesia is one of the leading initiatives under the framework of the 2014-2020 EU-Indonesia cooperation. ARISE Plus Indonesia mainly works to strengthen EU-Indonesia cooperation, the program abbreviated as ARISE Plus Indonesia is a 5-year grant program worth 10 million Euros or around Rp. 168 billion to improve export competitiveness and Indonesia's integration in global value chains. The European Union is the third largest investor in Indonesia with foreign direct investment of EUR 1.28 billion, after Malaysia and Singapore based on data from the Investment Coordinating Board (BKPM). The European Union provides grants to Indonesia so that Indonesian products can be competitive in the international market, and the European Union also needs Indonesian products to support the needs of their country. Keywords: Grants, Indonesia-European Union Cooperation, ARISE Plus Indonesia